C-TaC nested composite material and preparation method thereof
By preparing C-TaC nested composite materials, the problem of oxidation of graphite materials at high temperatures is solved, the density and oxidation resistance of the material are improved, and its reliability and durability in extreme environments are enhanced.
Patent Information
- Application Number
- CN202411735996.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Graphite materials are prone to oxidation at high temperatures, resulting in reduced service life and performance. It is difficult for existing modification methods to effectively match the thermal expansion coefficient of graphite.
Using the design concept of C-TaC nested composite materials, the nested composite materials are prepared by preparing suspensions of TaC powder, carbon powder and metal sintering agents, and the reaction sintering method is used to prepare nested composite materials, so that the TaC components can tightly fill graphite pores, improving the density of the material and the matching of thermal expansion coefficient.
It effectively improves the density and oxidation resistance of graphite materials, reduces the difference in thermal expansion coefficient, and enhances the reliability and durability of the materials in extreme environments.
Smart Images

Figure BDA0005162312780000101 
Figure HDA0005162312930000011 
Figure HDA0005162312930000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphite modification, in particular to a C-TaC (carbon-tantalum carbide) nested composite material and a preparation method thereof. Background Art
[0002] Graphite is the most common thermal field material with excellent high temperature resistance, thermal shock resistance and heat resistance. In the artificial graphite molding process, it is inevitable that there are a large number of micropores inside the graphite, which are the activation points of violent oxidation reactions at high temperatures, which will greatly reduce the service life and performance of graphite. Therefore, it is extremely necessary to improve the antioxidant properties of graphite products. Traditional modification methods include: matrix modification method, surface coating method, and solution impregnation method. Among them, the solution impregnation method is to impregnate the graphite products and then heat treat them to convert the impregnant into an antioxidant substance, while the acid salt impregnant has limited high temperature resistance. The surface coating method can construct an oxygen barrier layer, a glassy sealing layer, and a bonding layer on the graphite surface, and each layer coordinates with each other to achieve the most effective overall antioxidant property. However, due to the low thermal expansion coefficient of graphite materials, the thermal expansion coefficient and melting point of silicon-based ceramic coatings, oxide ceramic layers, and carbon-based ceramic coatings cannot be well matched with graphite under the repeated heating and cooling process of 1000℃-3000℃. Summary of the invention
[0003] The first aspect of the present invention provides a method for preparing a C-TaC nested composite material, comprising the following steps: providing solid particles, a dispersant and a solvent, mixing the solid particles uniformly, adding the dispersant and the solvent, and ultrasonically mixing them uniformly to obtain a C-TaC suspension;
[0004] The C-TaC suspension is treated by a reaction sintering method to obtain a C-TaC nested composite material;
[0005] The solid particles include TaC powder, carbon powder and metal sintering agent, and the weight ratio of the TaC powder, carbon powder and metal sintering agent is (3-10): (1-6): (0.3-3).
[0006] The components of the C-TaC suspension include: 5%-30% solid particles, 2%-20% dispersant, and 60%-90% solvent.
[0007] The components of the suspension include: 5%-30% solid particles, 2%-20% dispersant, and 60%-90% solvent;
[0008] Preferably, the C-TaC suspension comprises, by weight percentage, 10%-25% of solid particles, 2%-10% of dispersant, and the balance of solvent.
[0009] Further preferably, the C-TaC suspension comprises, by weight percentage, 15%-25% of solid particles, 2%-5% of dispersant, and the balance of solvent.
[0010] Preferably, the weight ratio of the TaC powder, carbon powder and metal sintering agent is (4-8): (1-6): (0.5-1.5).
[0011] Further preferably, the weight ratio of the TaC powder, carbon powder and metal sintering agent is 6:(1-6):1.
[0012] The average particle size of the TaC powder is 0.5 μm-20 μm, the average particle size of the carbon powder is 10 nm-80 nm, and the average particle size of the metal sintering agent is 20 nm-100 nm.
[0013] Preferably, the average particle size of the TaC powder is 0.5 μm-10 μm, the average particle size of the carbon powder is 10 nm-60 nm, and the average particle size of the metal sintering agent is 20 nm-60 nm.
[0014] Further preferably, the average particle size of the TaC powder is 1 μm-10 μm, the average particle size of the carbon powder is 10 nm-40 nm, and the average particle size of the metal sintering agent is 30 nm-60 nm.
[0015] As an example, the average particle size of the TaC powder may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0016] As an example, the average particle size of the carbon powder may be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.
[0017] As an example, the average particle size of the metal sintering agent may be 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, or 60 nm.
[0018] The metal sintering agent is selected from at least one of Fe, Cr, Mn, Mo, V, W, Ni and Cu.
[0019] The solvent includes at least one of ethanol, isopropanol, n-butanol, methoxypropanol, ethoxypropanol and diacetone alcohol.
[0020] The dispersant includes at least one of polyvinyl butyral, hydrogenated nitrile rubber and ethylene-vinyl acetate copolymer.
[0021] The applicant has found that a suspension is prepared, wherein the solid particles include TaC powder, carbon powder, and a metal sintering agent, and the weight ratio of TaC powder, carbon powder, and metal sintering agent is limited to (3-10): (1-6): (0.3-3), which can be used to prepare a C-TaC nested composite material, so that crystalline graphite and TaC polycrystalline are nested with each other, thereby effectively improving the density and reducing the difference in thermal expansion coefficient of the substrate. The TaC component densely fills the graphite pores, and there are no cracks and holes on the surface and cross-section of the material, so that the components are very tightly combined. TaC has extremely high thermochemical stability and good chemical and mechanical compatibility with graphite. Adding TaC components to graphite or preparing TaC coatings can effectively enhance its anti-oxidation, anti-corrosion, wear resistance and mechanical properties. The product of TaC under high-temperature ablation is Ta2O5 melt, which has a filling and blocking effect on the particle gaps and cracks caused by oxidation, and can be applied to the fields of ultra-high temperature hot end components of aerospace and the growth of third-generation semiconductor single crystals. However, if only a single TaC coating is prepared, the anti-oxidation layer will easily fail due to insufficient density of the coating and the difference in thermal expansion coefficient with the substrate. Therefore, the design concept of C-TaC nested composite materials will overcome this problem to a certain extent and improve the reliability and durability of the material in extreme environments.
[0022] The method comprises the following steps: mixing TaC powder, carbon powder and metal sintering agent uniformly, adding dispersant and solvent, and performing ultrasonic mixing uniformly.
[0023] The specific method of ultrasonication includes: ultrasonication for 5s-20s every 5s-20s, and ultrasonication for 150 times-300 times.
[0024] Preferably, the specific method of ultrasound includes: ultrasound for 5s-15s every 5s-15s, ultrasound 160 times-300 times.
[0025] Further preferably, the specific method of ultrasound includes: ultrasound every 7s-15s, ultrasound for 7s-15s, ultrasound 160 times-250 times.
[0026] The preparation of the suspension comprises the following steps: uniformly mixing TaC powder, carbon powder and metal sintering agent, adding dispersant and solvent, and uniformly mixing by ultrasonication.
[0027] The specific method of ultrasonication includes: ultrasonication for 5s-20s every 5s-20s, and ultrasonication for 150 times-300 times.
[0028] Preferably, the specific method of ultrasound includes: ultrasound for 5s-15s every 5s-15s, ultrasound 160 times-300 times.
[0029] Further preferably, the specific method of ultrasound includes: ultrasound every 7s-15s, ultrasound for 7s-15s, ultrasound 160 times-250 times.
[0030] The C-TaC suspension is treated by a reaction sintering method to prepare a C-TaC nested composite material, wherein the reaction sintering method includes dry molding and wet molding.
[0031] The dry forming method specifically comprises the following steps:
[0032] The suspension is allowed to stand, and the supernatant is removed to form a suspension with a solid content of 60wt%-70wt%, and the suspension is dried to prepare a mixed powder;
[0033] Cold pressing the mixed powder into a sheet-like embryo;
[0034] The sheet-like green body is sintered.
[0035] Preferably, the method comprises the following steps:
[0036] S1, allowing the suspension to stand, removing the supernatant to form a suspension with a solid content of 60wt%-70wt%, and drying the suspension to prepare a mixed powder;
[0037] S2, cold pressing the mixed powder into a sheet-like embryo;
[0038] S3, sintering the sheet-like green body.
[0039] The drying adopts a step-by-step temperature increase method, which includes: drying at 30°C-70°C for 2h-5h, drying at 70°C-90°C for 1h-3h, and drying at 90°C-120°C for 0.5h-2h.
[0040] Preferably, the gradually increasing temperature method includes: drying at 40°C-70°C for 3h-5h, drying at 75°C-90°C for 1h-2h, and drying at 90°C-110°C for 0.5h-1.5h.
[0041] Further preferably, the gradually increasing temperature method comprises: drying at 40°C-60°C for 3h-4h, drying at 75°C-85°C for 1.5h-2h, and drying at 90°C-110°C for 0.5h-1h.
[0042] The shape of the mixed powder includes a sphere, and the average particle size of the mixed powder is 200nm-500nm.
[0043] Preferably, the average particle size of the mixed powder is 200nm-400nm.
[0044] More preferably, the average particle size of the mixed powder is 250nm-400nm.
[0045] The thickness of the sheet-like embryo body is 200 μm-500 μm.
[0046] Preferably, the thickness of the sheet-like embryo body is 200 μm-400 μm.
[0047] More preferably, the thickness of the sheet-like embryo body is 250 μm-400 μm.
[0048] The sintering temperature rising procedure includes: first heating to 1700-2200°C at a heating rate of 2°C / min-10°C / min, keeping warm for 5min-25min, then heating to 2300-2700°C at a heating rate of 1°C / min-6°C / min, keeping warm for 40min-100min, and cooling naturally.
[0049] Preferably, the sintering temperature rising program includes: first heating to 1900℃-2200℃ at a heating rate of 2℃ / min-8℃ / min, keeping warm for 5min-20min, then heating to 2300℃-2600℃ at a heating rate of 1℃ / min-5℃ / min, keeping warm for 40min-80min, and cooling naturally.
[0050] Further preferably, the sintering temperature rising program includes: first heating to 1900℃-2100℃ at a heating rate of 3℃ / min-7℃ / min, keeping warm for 5min-15min, then heating to 2400℃-2600℃ at a heating rate of 1℃ / min-4℃ / min, keeping warm for 50min-80min, and cooling naturally.
[0051] A C-TaC nested composite coating is prepared on the surface of a graphite part. The compatibility of the C component and TaC makes the thermal expansion coefficient of the coating slightly higher than that of graphite but lower than the theoretical thermal expansion coefficient of TaC. At present, high thermal expansion coefficient graphite is often customized in CVD-TaC coated graphite parts to reduce the thermal mismatch problem with the TaC coating, but the cost of graphite is relatively high. The blocks and coated parts prepared by the present application through specific dry processes and wet processes can achieve full density while reducing production costs. The reason may be that the C component can fill the pores formed in the TaC coating or ceramic sintering process to a limited extent, so the overall coating or ceramic is denser.
[0052] The wet forming method specifically comprises the following steps:
[0053] Applying the suspension on a graphite piece and drying it to form a graphite piece coated with a pre-coating layer;
[0054] The graphite member coated with the pre-coating layer is sintered.
[0055] Preferably, the method comprises the following steps:
[0056] Step 1, applying the suspension on a graphite piece and drying it to form a graphite piece coated with a pre-coating layer;
[0057] Step 2: sintering the graphite part coated with the pre-coating layer.
[0058] The thickness of the pre-coating layer is 10 μm-80 μm.
[0059] Preferably, the thickness of the pre-coating layer is 10 μm-60 μm.
[0060] Further preferably, the thickness of the pre-coating layer is 10 μm-50 μm.
[0061] The second aspect of the present application provides a C-TaC nested composite material, wherein the average linear thermal expansion coefficient (GB / T 4399-2008) of the C-TaC nested composite material at 100°C-600°C, 350°C-450°C and 1000°C-1100°C is 5.1E -6 ·K -1 -6.2E -6 ·K -1 .
[0062] Beneficial Effects
[0063] 1. In the preparation method of the C-TaC nested composite material of the present application, the solid particles include TaC powder, carbon powder, and a metal sintering agent, and the weight ratio of TaC powder, carbon powder, and metal sintering agent is limited to (3-10): (1-6):
[0064] (0.3-3), so that the TaC component densely fills the graphite pores, there are no cracks and holes on the surface and cross-section of the material, and the components are very tightly combined, thereby effectively improving the density and reducing the difference in thermal expansion coefficient of the substrate.
[0065] 2. The preparation method of the C-TaC nested composite material in the present application is to first prepare a suspension, and based on the suspension, either a wet molding process or a dry molding process can be used, so that the preparation process has the characteristics of diversity and flexibility.
[0066] 3. In the wet forming process of the present application, the pre-coating layer is a product of graphite coating and drying, and the coating layer is formed after sintering, which improves the application scope of the preparation process.
[0067] 4. In the dry forming process of the present application, by removing the upper clear liquid after the suspension is allowed to stand, a suspension with a solid content of 60wt%-70wt% is formed, which can improve the dispersion uniformity of various solid phases in the mixed powder and is conducive to improving the subsequent drying efficiency.
[0068] 5. In the dry forming process of the present application, the drying adopts a gradual heating method, which includes: drying at 30℃-70℃ for 2h-5h, drying at 70℃-90℃ for 1h-3h, and drying at 90℃-120℃ for 0.5h-2h, which can further improve the drying efficiency and obtain a uniform mixed powder with atomic dispersion level distribution.
[0069] 6. The C-TaC nested composite material prepared in this application can improve the service life and performance of graphite. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is the SEM image of the C-TaC nested composite material prepared in Example 1 (scale: 200 μm).
[0071] Figure 2 This is the SEM image of the C-TaC nested composite material prepared in Example 1 (scale 40 μm).
[0072] Figure 3 The Raman spectrum of the C-TaC nested composite material prepared in Example 1.
[0073] Figure 4 This is the SEM image of the C-TaC nested composite material prepared in Example 2 (scale: 100 μm).
[0074] Figure 5 This is the SEM image of the C-TaC nested composite material prepared in Example 2 (scale 40 μm).
[0075] Figure 6 This is the SEM image of the C-TaC nested composite material prepared in Example 3 (scale 100m).
[0076] Figure 7 This is the SEM image of the C-TaC nested composite material prepared in Example 3 (scale: 20 μm).
[0077] Figure 8 SEM image of a graphite piece coated with a 30 μm pre-coating layer prepared for Example 4 (cross section, scale 10 μm).
[0078] Fig. 9 for Figure 8 SEM image of the C-TaC nested composite coating graphite part obtained after sintering (cross section, scale 10 μm).
[0079] Fig.10 This is the SEM image of the C-TaC nested composite coating graphite piece prepared in Example 4 (cross section, scale 50 μm).
[0080] Fig.11 This is the SEM image of the C-TaC nested composite coating graphite piece prepared in Example 4 (surface, scale 10 μm).
[0081] Fig.12 SEM image of the C-TaC nested composite material prepared in Comparative Example 1 (scale: 100 μm).
[0082] Fig.13 SEM image of the C-TaC nested composite material prepared in Comparative Example 1 (scale 10 μm).
[0083] Fig.14 SEM image of the C-TaC nested composite material prepared in Comparative Example 2 (scale: 10 μm).
[0084] Fig.15 SEM image of the C-TaC nested composite material prepared in Comparative Example 2 (scale 4 μm).
[0085] Fig.16 SEM image of the C-TaC nested composite material prepared in Comparative Example 2 (scale 40 μm).
[0086] Fig.17 SEM image of the C-TaC nested composite material prepared in Comparative Example 3 (scale 40 μm). DETAILED DESCRIPTION
[0087] The invention provides a method for preparing a C-TaC nested composite material and a method for preparing the C-TaC nested composite material. The main components of the prepared composite material are crystalline graphite and TaC polycrystal, which are nested with each other. Different from traditional gradient composite coatings, the TaC component densely fills the graphite pores, and there are no cracks and holes on the surface and cross-section of the material. This design effectively improves the density between the components and reduces the difference in thermal expansion coefficient of the substrate, thereby enhancing the overall performance and stability of the material.
[0088] Example 1
[0089] A method for preparing a C-TaC nested composite material comprises the following steps:
[0090] The TaC powder, carbon powder and metal sintering agent were mixed uniformly, a dispersant and a solvent were added, and ultrasonic cell disruptor was used at 60% power (horn type 20, 20.5KHZ, 1200W), ultrasonicated for 10 seconds every 10 seconds, and ultrasonicated for 200 times to obtain a uniformly mixed suspension;
[0091] The C-TaC suspension is treated by dry molding to obtain a C-TaC nested composite material.
[0092] The solid particles are TaC powder, carbon powder and metal sintering agent.
[0093] The components of the C-TaC suspension are: 15% solid particles, 2% dispersant (polyvinyl butyral, viscosity 15-18s, Aladdin, P294391-500g), and the balance is made up of solvent (anhydrous ethanol); the solid particles include TaC powder (average particle size 3μm, purity 99.95%, Aladdin, T111043-50g), carbon powder (average particle size 30nm, purity 99.5%, Aladdin, C109965-500g), and metal sintering agent (iron powder, average particle size 50nm, purity 99.9%, McLean), and the weight ratio of the TaC powder, carbon powder, and metal sintering agent is 6:6:1.
[0094] The dry forming process comprises the following steps:
[0095] S1, after the uniformly mixed suspension is allowed to stand, the supernatant is removed to form a suspension with a solid content of 65 wt%, and the suspension is dried at 50° C. for 3 h, 80° C. for 2 h, and 100° C. for 1 h in sequence to prepare a mixed powder;
[0096] S2, selecting 0.25 g of the mixed powder and putting it into a mold for cold pressing, and pressing it into a sheet-like embryo with a thickness of 300 μm under a pressure of 2.5 MPa;
[0097] S3, placing the sheet-like embryo into a graphite crucible, and transferring it to a vacuum graphite induction furnace, in a slightly positive pressure argon atmosphere, heating to 2000°C at a heating rate of 5°C per minute, keeping warm for 10 minutes, then heating to 2500°C at a heating rate of 2°C per minute, keeping warm for 60 minutes, and cooling naturally, thereby preparing a composite material sheet with a thickness of 310 μm.
[0098] Example 2
[0099] The specific implementation is the same as that of Example 1; the difference is that the weight ratio of TaC powder, carbon powder and metal sintering agent in Example 2 is 6:3:1.
[0100] Example 3
[0101] The specific implementation is the same as that of Example 1; the difference is that the weight ratio of TaC powder, carbon powder and metal sintering agent in Example 3 is 6:1:1.
[0102] Example 4
[0103] A method for preparing a C-TaC nested composite material is the same as that in Example 3, except that the C-TaC suspension is treated by wet molding to obtain the C-TaC nested composite material, which specifically comprises the following steps:
[0104] Step 1, applying the suspension on a graphite piece and drying it to form a graphite piece coated with a 30 μm pre-coating layer;
[0105] Step 2: Place the graphite part coated with the pre-coating layer into a graphite crucible, transfer it to a vacuum graphite induction furnace, and heat it to 2000°C at a heating rate of 5°C per minute in a slightly positive pressure argon atmosphere, keep it warm for 10 minutes, then heat it to 2500°C at a heating rate of 2°C per minute, keep it warm for 60 minutes, and cool it down naturally.
[0106] Comparative Example 1
[0107] The specific implementation is the same as that of Example 1; the difference is that the TaC powder in Comparative Example 1 is replaced by Ta powder.
[0108] Comparative Example 2
[0109] The specific implementation is the same as that of Example 1; the difference is that in Comparative Example 2, the weight ratio of TaC powder, carbon powder and metal sintering agent is 1:1:1.
[0110] Comparative Example 3
[0111] The specific implementation is the same as Example 1; the difference is that in Comparative Example 3, the weight ratio of TaC powder, carbon powder and metal sintering agent is 6:3:2.
[0112] Performance testing methods and data
[0113] Average thermal expansion coefficient test; Instrument: thermal expansion instrument NETZSCH DIL 402C; Test basis: GB / T 4399-2008 Determination of thermal expansion characteristic parameters of metal materials; Test environment: temperature: 25°C, humidity 45% RH; Atmosphere: high-purity nitrogen, flow rate: 70mL / min; Sample size: 25*5*5mm (length*width*thickness); Program conditions: 25°C-1200°C (5°C / min), the test results are shown in Table 1, the average linear thermal expansion coefficient (100-600°C, 350-450°C, 1000-1100°C) of the C-TaC nested composite material prepared by the present application is greater than the isostatic graphite on the market, and lower than the average thermal expansion coefficient of tantalum carbide. It can be seen that compared with traditional graphite materials, the C-TaC nested composite material exhibits more superior performance in high-temperature applications, and is particularly suitable for use as a substrate for the growth of high thermal expansion coefficient carbide coatings. This property enhances the stability and reliability of the material in high temperature environments and has good application prospects.
[0114] The sample prepared in Example 1 was subjected to Raman spectroscopy test. Figure 3 As shown, the peaks of TaC and high-purity graphite can be observed, confirming the successful preparation of the C-TaC nested composite material.
[0115] The samples prepared in Examples 1-4 were subjected to SEM test, wherein the C-TaC nested composite material prepared in Example 1 was Figure 1 As shown, the thickness is about 310 μm. Figure 2 As shown, the silver area is the TaC component, showing step-like growth without holes and cracks, and the black area is crystalline graphite. The two are tightly combined and randomly distributed, and the graphite component is significantly more than the TaC component; the C-TaC nested composite material prepared in Example 2, such as Figure 4-5 As shown, the ratio of TaC component and crystalline graphite in the composite material is close; the C-TaC nested composite material prepared in Example 3 is as follows Figure 6-7 As shown, the TaC component in the composite material is obviously more; the C-TaC nested composite material prepared in Example 4 is as follows Fig. 9 and Fig.11 As shown, the surface morphology of the composite coating on the graphite substrate is similar to that of the composite sheet in Example 3. Figure 8 As shown in Figure 2, the pre-coating layer and the graphite substrate are clearly separated. Fig.10As shown, it can be seen that the TaC coating has excellent crystallinity and large blocks, while the crystalline graphite is relatively messily covered and filled in the TaC surface and gaps. Through these SEM test results, it can be seen that the microstructural characteristics of the C-TaC nested composite materials in different embodiments, as well as the interaction and distribution between the components. This provides an important reference for subsequent performance analysis.
[0116] like Figure 12-13 As shown in the figure, TaC powder is replaced by Ta powder. The prepared C-TaC nested composite material has poor crystallinity, many holes and cracks, and is not dense, which indicates that the application of Ta powder in this system is not conducive to improving the performance of the material.
[0117] like Figure 14-16 As shown in the figure, when the Fe content increases sharply, the prepared composite material, including the coating and the block, can be divided into a three-layer structure. The top layer is crystalline graphite, containing sporadic TaC components, with a rough and uneven surface, and the thickness of the graphite polycrystalline layer is 85 microns; the middle layer is iron, and the low melting point of iron can easily cause the melting of iron at high temperature and damage the coating; the bottom layer is a composite material of graphite, iron, and TaC. It can be seen that excessive iron increases volatile impurities and reduces purity. The original C-TaC nested structure has changed under the intervention of Fe, which may lead to a decrease in the performance of the material. Therefore, when designing composite materials, it is necessary to reasonably control the proportion of each component to ensure that the characteristics and functions of the composite material can be effectively maintained.
[0118] like Figure 14-16 As shown, the Fe content is doubled based on the formula of Example 2, so that the surface of the prepared composite material is still uniformly distributed with TaC and C, but a large amount of Fe (dark color) is observed at the cross section as a bonding layer connecting TaC grains (gray), and the C component is greatly reduced, which no longer meets the definition of C-TaC nested composite material.
[0119] It can be seen that the C and Fe content in the formula is crucial to the formation of a uniform C-TaC nested composite material. Appropriate C content helps maintain the integrity of the nested structure and ensures good bonding between TaC grains; while excessive Fe may lead to a reduction in the C component, thereby destroying the ideal structure and properties of the composite material. Therefore, in the formulation design of the material, the ratio of C and Fe must be carefully controlled to achieve the optimal microstructure and desired properties.
[0120] Table 1
[0121]
Claims
1. A method for preparing a C-TaC nested composite material, characterized in that: The following steps are involved: Providing solid particles, a dispersant and a solvent, mixing the solid particles uniformly, adding the dispersant and the solvent, and ultrasonically mixing them uniformly to obtain a C-TaC suspension; The C-TaC suspension is treated by a reaction sintering method to obtain a C-TaC nested composite material; The solid particles include TaC powder, carbon powder and metal sintering agent, and the weight ratio of the TaC powder, carbon powder and metal sintering agent is (3-10): (1-6): (0.3-3).
2. The method for preparing the C-TaC nested composite material according to claim 1, characterized in that: The average particle size of the TaC powder is 0.5 μm-20 μm, the average particle size of the carbon powder is 10 nm-80 nm, and the average particle size of the metal sintering agent is 20 nm-100 nm.
3. The method for preparing the C-TaC nested composite material according to claim 1, characterized in that: Calculated by weight percentage, the components in the C-TaC suspension include: solid particles 5%-30%, dispersant 2%-20%, and solvent 60%-90%.
4. The method for preparing the C-TaC nested composite material according to claim 1, characterized in that: The specific method of ultrasonication includes: ultrasonication for 5s-20s every 5s-20s, and ultrasonication for 150 times-300 times.
5. The method for preparing the C-TaC nested composite material according to claim 4, characterized in that: The reaction sintering method includes dry forming and wet forming.
6. The method for preparing the C-TaC nested composite material according to claim 5, characterized in that: The dry forming comprises the following steps: The suspension is allowed to stand and then the supernatant is removed to form a suspension with a solid content of 60wt%-70wt%, and the suspension is dried to prepare a mixed powder; Cold pressing the mixed powder into a sheet-like embryo; The sheet-like green body is sintered.
7. The method for preparing the C-TaC nested composite material according to claim 6, characterized in that: The drying adopts a step-by-step heating method, which includes: drying at 30°C-70°C for 2h-5h, drying at 70°C-90°C for 1h-3h, and drying at 90°C-120°C for 0.5h-2h; the shape of the mixed powder includes a sphere, and the average particle size of the mixed powder is 200nm-500nm.
8. The method for preparing the C-TaC nested composite material according to claim 6, characterized in that: The sintering temperature rising procedure includes: first heating to 1700-2200°C at a heating rate of 2°C / min-10°C / min, keeping warm for 5min-25min, then heating to 2300-2700°C at a heating rate of 1°C / min-6°C / min, keeping warm for 40min-100min, and cooling naturally.
9. The method for preparing the C-TaC nested composite material according to claim 5, characterized in that: The wet forming comprises the following steps: Applying the suspension on a graphite piece and drying it to form a graphite piece coated with a pre-coating layer; The graphite member coated with the pre-coating layer is sintered.
10. A C-TaC nested composite material obtained by the preparation method according to claims 1-9, characterized in that: The average linear thermal expansion coefficient of the C-TaC nested composite material at 100°C-600°C, 350°C-450°C and 1000°C-1100°C is 5.1E -6 ·K -1 -6.2E -6 ·K -1 .
Citation Information
Patent Citations
Low-cost tantalum carbide coating preparation method
CN106699228A
Method for preparing tantalum carbide coating on surface of carbon material
CN116332678A
Preparation method of TaC coating, graphite structural component and silicon carbide crystal growth device
CN117069516A
Tac-coated graphite member
JP2020011866A
Method for producing coated substrates, coated substrate, and use thereof
US20240336536A1